PATHOPHYSIOLOGY, DIAGNOSIS, AND MANAGEMENT OF NEUROPATHIC PAIN - Puteri, Lintang Firdhani Nabila; Rahmawati, Dessika (Journal of Pain, Headache and Vertigo, 2025)
Background: Neuropathic pain is a type of chronic pain resulting from lesions or disorders of the somatosensory nervous system. This condition is often difficult to recognize and manage due to the complexity of its mechanisms and the variation in clinical symptoms. Objective: This article aims to review the pathophysiological mechanisms, diagnostic approaches, and management strategies for neuropathic pain based on current scientific literature. Result: The main mechanisms of neuropathic pain include ectopic activity, central sensitization, dysfunction of descending inhibitory pathways, and glial cell activation. Diagnosis is established through a combination of detailed history taking, neurological examination, screening tools such as DN4, and supporting investigations such as EMG-NCV, QST, skin biopsy, ultrasonography, and MRI. Pharmacological therapy includes the use of tricyclic antidepressants, SNRIs, anticonvulsants, and topical agents, with an individualized and stepwise approach. Advanced imaging techniques such as MRI and CT play a critical role in detecting structural lesions. Conclusion: The diagnostic and therapeutic approaches to neuropathic pain should be multimodal and mem-based. Integration of clinical and supporting examinations is key to improving diagnostic accuracy and therapeutic effectiveness.